Loading in 5 sec....

More Functions and SetsPowerPoint Presentation

More Functions and Sets

- By
**liam** - Follow User

- 286 Views
- Updated On :

More Functions and Sets Rosen 1.8 B A S f(a) a Inverse Image Let f be an invertible function from set A to set B. Let S be a subset of B. We define the inverse image of S to be the subset of A containing all pre-images of all elements of S. f -1 (S) = {a A | f(a) S} B f f A -1

Related searches for Functions

Download Presentation
## PowerPoint Slideshow about 'Functions' - liam

**An Image/Link below is provided (as is) to download presentation**

Download Policy: Content on the Website is provided to you AS IS for your information and personal use and may not be sold / licensed / shared on other websites without getting consent from its author.While downloading, if for some reason you are not able to download a presentation, the publisher may have deleted the file from their server.

- - - - - - - - - - - - - - - - - - - - - - - - - - E N D - - - - - - - - - - - - - - - - - - - - - - - - - -

Presentation Transcript

### More Functions and Sets

Rosen 1.8

A

S

f(a)

a

Inverse Image- Let f be an invertible function from set A to set B. Let S be a subset of B. We define the inverse image of S to be the subset of A containing all pre-images of all elements of S.
- f-1(S) = {aA | f(a) S}

f

f

A

-1

a2

b1

b2

a1

S

f-1(S)

Let f be an invertible function from A to B. Let S be a subset of B. Show that f-1(S) = f-1(S)What do we know?

f must be 1-to-1 and onto

Let f be an invertible function from A to B. Let S be a subset of B. Show that f-1(S) = f-1(S)

Proof: We must show that f-1(S) f-1(S) and that f-1(S) f-1(S) .

Let x f-1(S). Then xA and f(x) S. Since f(x) S, x f-1(S). Therefore x f-1(S).

Now let x f-1(S). Then x f-1(S) which implies that f(x) S. Therefore f(x) S and x f-1(S)

Let f be an invertible function from A to B. Let S be a subset of B. Show that f-1(S) = f-1(S)

Proof:

f-1(S) = {xA | f(x) S} Set builder notation

= {xA | f(x) S} Def of Complement

= f-1(S) Def of Complement

Floor and Ceiling Functions subset of B. Show that f

- The floor function assigns to the real number x the largest integer that is less than or equal to x. x
- x = n iff n x < n+1, nZ
- x = n iff x-1 < n x, nZ
- The ceiling function assigns to the real number x the smallest integer that is greater than or equal to x. x
- x = n iff n-1 < x n, nZ
- x = n iff x n < x+1, nZ

Examples subset of B. Show that f

0.5 = 1

0.5 = 0

-0.3 = 0

-0.3 = -1

6 = 6

6 = 6

-3.4 = -3

3.9 = 3

Prove that subset of B. Show that fx+m = x + m when m is an integer.

Proof: Assume that x = n, nZ.

Therefore n x < n+1.

Next we add m to each term in the inequality to get n+m x+m < n+m+1.

Therefore x+m = n+m = x + m

x = n iff n x < n+1, nZ

n subset of B. Show that f

n+1

Let xR. Show that 2x = x + x+1/2Proof: Let nZ such that x = n. Therefore

n x < n+1. We will look at the two cases:

x n + 1/2 and x < n + 1/2.

Case 1: x n + 1/2

Then 2n+1 2x < 2n+2, so 2x = 2n+1

Also n+1 x + 1/2 < n+2, so x + 1/2 = n+1

2x = 2n+1 = n + n+1 = x + x+1/2

Let x subset of B. Show that fR. Show that 2x = x + x+1/2

Case 2: x < n + 1/2

Then 2n 2x < 2n+1, so 2x = 2n

Also n x + 1/2 < n+1, so x + 1/2 = n

2x = 2n = n + n = x + x+1/2

Characteristic Function subset of B. Show that f

Let S be a subset of a universal set U. The characteristic function fS of S is the function from U to {0,1}such that fS(x) = 1 if xS and fS(x) = 0 if xS.

Example: Let U = Z and S = {2,4,6,8}.

fS(4) = 1

fS(10) = 0

Let A and B be sets. Show that for all x, subset of B. Show that ffAB(x) = fA(x)fB(x)

Proof: fAB(x) must equal either 0 or 1.

Suppose that fAB(x) = 1. Then x must be in the intersection of A and B. Since x AB, then xA and xB. Since xA, fA(x)=1 and since xB fB(x) = 1. Therefore fAB = fA(x)fB(x) = 1.

If fAB(x) = 0. Then x AB. Since x is not in the intersection of A and B, either xA or xB or x is not in either A or B. If xA, then fA(x)=0. If xB, then fB(x) = 0. In either case fAB = fA(x)fB(x) = 0.

Let A and B be sets. Show that for all x, f subset of B. Show that fAB(x) = fA(x) + fB(x) - fA(x)fB(x)

Proof: fAB(x) must equal either 0 or 1.

Suppose that fAB(x) = 1. Then xA or xB or x is in both A and B. If x is in one set but not the other, then fA(x) + fB(x) - fA(x)fB(x)= 1+0+(1)(0) = 1. If x is in both A and B, then fA(x) + fB(x) - fA(x)fB(x) = 1+1 – (1)(1) = 1.

If fAB(x) = 0. Then xA and xB. Then fA(x) + fB(x) - fA(x)fB(x)= 0 + 0 – (0)(0) = 0.

Let A and B be sets. Show that for all x, f subset of B. Show that fAB(x) = fA(x) + fB(x) - fA(x)fB(x)

A B AB fAB(x) fA(x) + fB(x) - fA(x)fB(x)

1 1 1 1 1+1-(1)(1) = 1

1 0 1 1 1+0-(1)(0) = 1

0 1 1 1 0+1-(0)(1) = 1

0 0 0 0 0+)-(0)(0) = 0

Download Presentation

Connecting to Server..